Amino acid metabolism of the thermophilic acetogen Thermacetogenium phaeum - Yanlin Cai; Andreas Marquardt; David Schleheck; Nicolai Müller (PLoS ONE, 2025)
Anaerobic microbial degradation of the amino acids glycine and serine either occurs through enzymes of the so-called Stickland reaction or alternatively through the glycine cleavage system (GCS). In the mesophilic anaerobe Peptoclostridium acidaminophilum , initial glycine degradation proceeds through disproportionation to methylene tetrahydrofolate (THF) and acetyl-phosphate by GCS and glycine reductase. The thermophilic acetogen Thermacetogenium phaeum is able to utilize glycine, serine or threonine as sole carbon source, although it lacks genes for glycine reductase. In contrast, T. phaeum possesses genes for the GCS as well as for serine-converting enzymes, and the corresponding enzymes were specifically overabundant in the proteome and active. Among these enzymes, serine dehydratase was most active in serine-grown cells, even though its abundance in the proteome was comparably low. We suggest that two serine-converting enzyme systems (serine dehydratase, and the combination of glycine hydroxymethyltransferase and GCS) are used under different growth conditions: for breakdown of serine, T. phaeum most likely converts serine to pyruvate and ammonia by serine dehydratase, followed by acetate and ATP production via pyruvate dehydrogenase, phosphate acetyltransferase and acetate kinase. Electron carriers are then re-oxidized through CO 2 -fixation via the Wood-Ljungdahl pathway (WLP) of acetogenesis. When grown with glycine, the GCS most likely converts glycine to methylene-THF, which is then disproportionated to methenyl-THF and methyl-THF in the WLP. Glycine and serine both are excellent substrates for T. phaeum , yet in syntrophic cocultures with Methanothermobacter thermautotrophicus , acetate from glycine or serine degradation cannot be degraded further, as in syntrophic cultures with acetate as sole carbon source. This indicates an inhibitory or regulatory effect of glycine or serine degradation on acetate-degrading enzymes, resulting in the inability of T. phaeum to transition directly to syntrophic acetate oxidation after amino acid degradation.